Effect of chemical modified water hyacinth fiber with polyvinyl alcohol (PVA) and polymethyl methacrylate (PMMA) synthetic on mechanical properties of LDPE/NR/WHF composites - Tan, Soo Jin; Supri, Abdul Ghani, Dr.; Teh, Pei Leng (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.